Impact of Access to Mass Media and ICT on Knowledge of HIV Transmission During Pregnancy Among Women of Reproductive Age in the Republic of Fiji - Sri Musfiroh; Siti Difta Rahmatika; Fika Nurul Hidayah; Diyanah Kumalasary; Luisa Bainikoro (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Access to accurate health information plays a pivotal role in shaping women’s awareness and practices regarding HIV prevention, particularly during pregnancy. Mass media and information and communication technology (ICT) serve as crucial platforms for disseminating knowledge that can reduce mother-to-child transmission of HIV. This study aims to examine the impact of access to mass media and ICT on women’s knowledge of HIV transmission during pregnancy. This study utilized secondary data from the 2021 Multiple Indicator Cluster Survey (MICS) in Fiji, conducted by the Fiji Bureau of Statistics in collaboration with UNICEF. A total of 3,649 women aged 15–49 years were included after excluding missing values. The outcome variable was knowledge of HIV transmission during pregnancy, while main independent variables were access to mass media and ICT, along with sociodemographic factors. Data analysis consisted of univariate, Chi-square test, and binary logistic regression, with significance set at p <0.05. The findings revealed that only 59.36% of women correctly identified that HIV can be transmitted during pregnancy. The findings revealed that only 59.36% of women correctly identified that HIV can be transmitted during pregnancy. Several factors were significantly associated with HIV knowledge, including internet use, mobile phone ownership, reading newspapers, age group, marital status, and education. Among these, internet use and reading newspapers were found to substantially increase the likelihood of having HIV knowledge, while higher education and older age served as strong predictors. In contrast, women from the richest households and those who had never married showed lower odds of being knowledgeable about HIV transmission during pregnancy. Access to mass media, ICT, age, marital status, and education significantly influenced women’s knowledge of HIV transmission during pregnancy. These findings highlight the need to integrate HIV education into antenatal care, community programs, and digital platforms to improve maternal knowledge.